Effect of surgical training on outcome and hospital costs in coronary surgery. Issue 4 (1st April 2001) - Goodwin, A T; Birdi, I; Ramesh, T P J; Taylor, G J; Nashef, S A M; Dunning, J J; Large, S R
Abstract : BACKGROUND: There is a perceived conflict between the need for service provision and surgical training within the National Health Service (NHS). Trainee surgeons tend to be slower (thereby reducing theatre throughput), and may have more complications (increasing hospital stay and costs). OBJECTIVE: To quantify the effect of training on outcome and costs. DESIGN: Data on 2740 consecutive isolated coronary artery bypass (CABG) operations were analysed retrospectively. Redo and emergency procedures were excluded. The seniority of the operating surgeon was related to operating times, risk stratified outcome, and overall hospital costs. SETTING: Regional cardiothoracic surgery unit. MAIN OUTCOME MEASURES: Postoperative mortality; hospital costs. RESULTS: Consultants, senior trainees, intermediate trainees, and junior trainees performed 1524, 759, 434, and 23 procedures, respectively. Trainees at the three different levels were directly supervised by a consultant in 55%, 95%, and 100% of cases. The unadjusted mortalities were 3.2%, 2.0%, 2.3%, and 4.3%, respectively (NS). There were no significant differences between the groups with respect to time in the intensive care unit and length of hospital stay. The mean cost per patient was £6619, £6572, £6494, and £6404 (NS). CONCLUSIONS: Trainees performed 44.4% of all CABG operations. There was no detrimental effect on patient outcome, length of hospital stay, or overall hospital costs. There need be little conflict between service and training needs, even in hospitals with extensive training programmes.